2010
DOI: 10.1194/jlr.m004374
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of sphingosine kinase 1 alters access to substrate pools but does not affect the degradative fate of sphingosine-1-phosphate

Abstract: Sphingosine-1-phosphate (S1P) has emerged as a potent bioactive lipid with established roles in essential cellular processes such as vascular maturity, cell proliferation, traffi cking of immune cells, cytoskeletal rearrangement, invasion, and angiogenesis ( 1-3 ). Key to such diversity of functions lies in the ability of S1P to act as both an intracellular effector molecule and an extracellular ligand for a family of fi ve G protein-coupled receptors, S1PR 1-5 ( 4-7 ). S1P made within the cell can be secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…However, it is also likely that CIB1 can "override" the intrinsic mechanism of SK1 membrane binding and force it to the membrane as a function of the myristoyl-switch. It is also possible that interaction with CIB1 is dependent on SK1 membrane interaction and mutation of the hydrophobic patch disrupts SK1 membrane Activity of membrane-associated SK1 has been documented in several studies [17,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also likely that CIB1 can "override" the intrinsic mechanism of SK1 membrane binding and force it to the membrane as a function of the myristoyl-switch. It is also possible that interaction with CIB1 is dependent on SK1 membrane interaction and mutation of the hydrophobic patch disrupts SK1 membrane Activity of membrane-associated SK1 has been documented in several studies [17,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic action of sphingosine kinase is one possible regulatory process. Our group and others have suggested that sphingosine kinase, by consuming dihydrosphingosine, a precursor in the ceramide biosynthetic pathway, can regulate ceramide biosynthesis (13,18,19). Alternatively, regulatory subunits of SPT (3-5) may be involved in the serum-dependent regulation of ceramide biosynthesis.…”
Section: Ormdl Proteins and Additional Mechanisms Play A Role In The mentioning
confidence: 99%
“…H Incorporated into Ceramides-At the completion of the labeling protocol, cells were harvested directly on the plates with 2 ϫ 900 l of acidic methanol (150:1, v/v) and scraping and then transferred to 13 ϫ 100-mm glass tubes and sonicated in a bath sonicator to break up cell clumps. Total cellular lipids were extracted using a modified version of the method of Bligh and Dyer (27) as reported previously (13). The bottom organic phase was collected and dried under nitrogen and then spotted onto thin layer chromatography plates Partisil K6 (Silica Gel 60 Å, Whatman).…”
Section: Materials-silencermentioning
confidence: 99%
“…One explanation for the lack of suppression of sphingolipid biosynthesis by ORMDL3 overexpression is that described ( 12 ). Prior to extraction, a mixture of C17 sphingolipids was added to each sample (125 pmol/sample, Avanti sphingolipid mix #1) as internal standards.…”
Section: Overexpression Of Ormdl3 Suppresses the Activity Of Overexprmentioning
confidence: 99%
“…Sphingolipids were quantitated by HPLC electrospray ionization tandem mass spectrometry using selected ion monitoring on an ABSciex 4000 Q-Trap instrument as described previously (13)(14)(15). Total phospholipids for each sample were measured using a modifi ed Ames and Dubin assay ( 16 ), as previously described ( 12 ).…”
Section: Overexpression Of Ormdl3 Suppresses the Activity Of Overexprmentioning
confidence: 99%